Surgical outcomes in women with ovarian cancer - Elit, Laurie M. (Canadian Medical Association, 2008)
OBJECTIVE: We sought to assess whether the specialty of the surgeon or the hospital involved in the initial management of women with ovarian cancer determined the likelihood of unnecessary repeated abdominal surgery and long-term patient survival. METHODS: We conducted a population-based study involving women in Ontario, Canada, who had epithelial ovarian cancer treated initially with abdominal surgery between January 1996 and December 1998. We documented incident surgical cases using hospital contact data and the Ontario Cancer Registry. We obtained data on patient characteristics, clinical findings, surgical techniques and perioperative care from electronic administrative data records and patient charts. We performed regression analyses to assess the influence of surgeon and hospital specialization and of case volumes on the likelihood of repeat surgery and survival. We controlled for stage of disease and other factors associated with these outcomes. We also examined the relation between the adequacy of surgery and adjuvant chemotherapy with survival. RESULTS: A total of 1341 women met our inclusion criteria. Our analysis showed that repeat surgery was associated with the surgeon's discipline, younger patient age, well-differentiated tumours and early stage of disease. However, survival was not associated with the surgeon's discipline; rather, it was associated with advanced patient age, increasing comorbidities, advanced stage of disease, poorly differentiated tumours, urgent surgery and adjuvant chemotherapy. We observed a trend between inadequate surgery and a decreased likelihood of survival. CONCLUSION: Further study is needed to understand patterns of repeat surgery for ovarian cancer. Improved quality of operative reporting is required to classify surgical adequacy.